Identification of levels of resistance to cassava root rot disease (Botryodiplodia theobromae) in African landraces and improved germplasm using In vitro inoculation method - Onyeka, T.; Dixon, A.; Ekpo, E. (Springer, 2005)
Cassava root rot disease is an increasing problem in Africa where yield losses of about 80% have been recorded. We evaluated 290 African landraces and 306 improved genotypes from the germplasm collections of the International Institute of Tropical Agriculture (IITA), for sources of resistance using root slice laboratory assay. Disease severity was assessed quantitatively by direct percentage estimation (PS) and by use of a rating scale (RS). Both methods of assessment were compared for identification of variability in the germplasm, and genotypes were classified into response groups using an enlarged rank-sum method that combined the PS and RS assessments. The two scoring methods revealed continuous variation (P < 0.001) for resistance in the sets of germplasm. Disease assessments based on PS and RS were highly correlated in both the improved germplasm (r = 0.75) and the landraces (r = 0.72). Based on PS assessment, 50 improved genotypes (16.3%) and 53 landraces (18.3%) showed significantly lower disease scores than the resistant control. The rank-sum method separated each set of collections into highly resistant, resistant, moderately resistant, moderately susceptible, susceptible and highly susceptible groups. Fifty-nine improved genotypes (16.4%) and 61 African landraces (16.9%) were identified as either highly resistant or resistant. Generally, these genotypes exhibited resistance by limiting the growth of the pathogen (reduced amount of invaded surface area). This type of rate-reducing resistance is highly heritable and a quantitative trait which can be harnessed in breeding. Genotypes subsets were identified for further studies into the genetic basis of resistance to root rot disease.